TOURISM IN THE POST-COVID-19 WORLD: WHAT IS THE ROLE OF HUMAN RESOURCES IN TRACING THE PATHS TO RECOVERY - Eftimov, Lјupcho; Kitanovikj, Bojan (Faculty of Economics in East Sarajevo, 2023)
Tourism has been one of the most affected sectors due to the COVID-19 pandemic globally. As a result, human resources (HR) professionals have faced an onset of challenges, as well as, opportunities in the new normal. Therefore, this paper will shed a light on the vital practices that HR professionals in the tourism sector implement and understand how organizations in tourism manage their personnel in these disruptive times. The era of post-COVID-19 calls for resetting, restructuring, and redefining the role of HR, which strives to increase the employees’ skills and behaviors and drive forward organizational performance and efficiency. This is why, through theoretical and empirical exploration, this research will try to contribute to the identification of the key HR challenges for the postCOVID-19 world in this sector, the development of a theoretical model of strategic HR management, and highlighting future trends.
Keywords: Human resource management, Tourism, postCOVID-19